Smart Glove for Translating Arabic Sign Language “SGTArSL” - Dweik, Amal; Hanaa, Qasrawi; Dana, shawar (2021 31st International Conference on Computer Theory and Applications (ICCTA), 2021)
Deaf and mute people who use sign language often face serious communication problems with others. The Smart Glove for Translating Arabic Sign Language (SGTArSL) tries to address this problem by providing them with means of communications, especially with their families. SGTArSL uses small components to build a communication device to enhance the communication between deaf /mute people with others who, do not necessarily, understand their language; thus improving their independence. The system includes a smart glove that translates the Arabic Sign Language (ArSL) alphabets using only one hand by building a Printed Circuit Board (PCB) on a textile glove. The PCB uses a microcontroller and sensors to detect and classify the hand gesture, then sends the observed alphabet via Bluetooth as a text to a mobile application. In this paper, SGTArSL is successfully tested to enable people who communicate with deaf/mute users to understand their sign language alphabets.
Keywords: Arabic Sign Language, smart sensory glove